PENGARUH TEMPAT USAHA DAN KELENGKAPAN PRODUK TERHADAP PEMBELIAN ULANG KONSUMEN PADA SUPERMARKET BANGUNAN - Muhammad Ridwan; Noviarni Noviarni (JURNAL KOMPETITIF, 2021)
This study aims to determine, analyze and prove the effect of product and place completeness simultaneously and partially on repurchase at the Building Supermarket. The research site is located at the Cemerlang Jaya Building Supermarket. In this study, the population was all consumers who shopped at the supermarket of Gedung Cahaya Jaya totaling 50 consumers and the sample used was 50 consumers with the sampling technique used was saturated sampling. The results obtained from this study are that there is a significant effect of the place variable and the completeness of the product together on the repeat purchase variable as evidenced by the F test table which can be seen that sig is 0.001 from the significant level it means sig <0.05 which has the influence of place and completeness of the product together against repeat purchases. Meanwhile, partially obtained that there is a significant effect of the place variable on repeat purchases, as evidenced from the t-test analysis table it can be seen that for the place variable with a sig value of 0.003 From a significant value level (sig) <0.05, which means the place variable has an effect on purchases repeat. Furthermore, there is also a positive and significant effect of the product completeness variable on repeat purchases, as evidenced from the t test analysis table, it can be seen that for the product completeness variable, the sig value is 0.000. from the significant level value (sig) <0.05, which means that the product completeness variable has a significant effect on repeat purchases.